ANALISIS KINERJA EKSPOR RUMPUT LAUT PADA PT. KOSPERMINDO DI MAKASSAR - Abdul Khalik (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to determine the performance and contribution of exports to income-Original South Sulawesi. From the research, the authors showed that the volume of exports of seaweed for 5 (five) years (2009-2013) has increased, whereas in 2009-2010, the rate of export volume amounted to 54.56% seaweed and in 2011 increased by 54.77 % further back in 2012 increased by 87.84% and by 2013 an increase of 88.16%. This increase is caused by damage to a number of existing commodity seaweed in continental Europe due to the unfavorable climate that contributes to the high demand and the demand for commodities seaweed in Sulawesi - South increased sharply and supported by the improvement in global economic conditions due to the hurricane crisis dibelahan European continent. Contribution of export value averaged peningakatan for 5 (five) years where in 2009 s / d on average in 2013 increased by 28.97% in 2010 and increased in 2011 by 44.79%, then in 2012 s / d in 2013, respectively decreased by 10.23% in 2012 and in 2013 decreased by 39.40%. This decrease is caused by a surge in exports is too big so the impact on prices of seaweed has decreased in some countries in Europe.